New Frontiers in Polymer Synthesis - Kobayashi, Shiro (Springer, 2017)
In the past, most of the research on condensation polymerization was centered on development of methods for the synthesis of high molecular weight polymers. Therefore, reaction control in condensation polymerization was to pursue highly efﬁcient condensation reactions, because high molecular weight polymer is not obtained unless more than 99% of the degree of reaction is attained without side reactions, according to the basic principle established by Carothers and Flory [1–3]. Recent years have seen developments in chemoselective, regioselective, and stereoselective condensation polymerizations as those selective reactions have been developed in organic chemistry.